COMMON FACETS OF MUSEUM VIRTUAL SELF-PRESENTATION: EXPERIMENTING WITH INTERACTIVE IMAGE AND TEXT - Kasperiuniene, Judita; Norkute, Odeta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
In the modern world, all the museums, especially science and technology centers, seek transforming from storages of valuable historical objects to the knowledge exchange and construction places. This study aims to research official sites and social media channels of twenty European science and technology museums in order to understand how the virtual museum self-presentation is done. Using thematic analysis five common facets of the science and technology museum official site were coded: i) site interoperability; ii) home page; iii) first ten news; iv) science and education activities; v) information “about us”. All the data were anonymized. The study showed two contradicted science and technology museum virtual self-presentation behavior styles: orientation “Museum as a storage” and orientation “Visitor as a creator”. Researching how science and technology museums experimented with interactive image and text in their official web pages, museum social media site follower responses and museum ratings in social media, we expanded The Museum Visitor Experience Model with insights how the virtual self-presentation could help attracting museum visitors.